Economic and demographic assumptions of the public pension insurance system functioning - Đukić Gordana (Megatrend Revija, 2016)
The demographic transition is characterized by a decline in birth rates and fertility on the one hand, and an intense increase in the number of old people on the other hand. The intensity of demographic ageing is characteristic of certain countries, being more expressed in developed countries. In such a situation, negative economic consequences arise in the context of unemployment, due to a decreased number of young population and lower participation in the labour market, as well as in the domains of savings, capital market, health protection, pension system and institutional development. These consequences can be mitigated by the application of appropriate economic transition and macroeconomic policy. Demographic tendencies have a great impact on changes in the values of the pension system parameters. The dependence rate indicating the relation between the number of employed people and the number of pensioners, and the average replacement rate representing the relation between the average wage and average pension, are directly dependent on demographic changes and they directly affect the sustainability of the public pension insurance system.